38 Process Evaluation of the Praised 2, A Multi-Centre Randomised Controlled Trial (RCT) Testing the Clinical and Cost-Effectiveness of a Therapy Intervention Designed to Promote Activity and Independence Amongst People with Early Dementia or Mild Cognitive Impairment. (20th December 2019) - Di Lorito, Claudio; Pollock, Kristian; Harwood, Rowan; Booth, Vicky; Goldberg, Sarah; Van der Wardt, Veronika
Abstract: Introduction: The 'Promoting Activity, Independence and Stability in early dementia and cognitive impairment' (PrAISED 2) is a randomised controlled trial testing the effectiveness of an exercise and physical activity programme for people with mild cognitive impairment and early dementia. Parallel to the trial, our team is conducting a process evaluation, whose aims are to: 1. Determine the extent to which the programme is being delivered according to plan; 2. Gather feedback from the primary stakeholders on the quality of programme implementation. Here we present preliminary results from the PrAISED 2 process evaluation. Methods: The process evaluation comprises two studies: 1. An implementation study, examining the extent to which the programme is being delivered according to plan, which investigates Fidelity (i.e. the consistency of what is implemented with the planned intervention), Adaptations (i.e. alterations made to achieve better contextual fit), Dose (i.e. how much intervention is delivered) and Reach (i.e. the extent to which agents come into contact with the intervention). 2. A study on the mechanisms of impact and context, gathering feedback on the quality of implementation thorugh qualitative interviews with participants with dementia and their carers (as dyads) and therapists delivering the intervention. Results: The process evaluation is ongoing and results will be available in Autumn 2019. Conclusion: Results from the PrAISED 2 process evaluation will: enable the identification of the active ingredients within the intervention and explain how they are exerting their effect; explain discrepancies between expected and observed outcomes; help to understand how context influences outcomes; provide crucial insights to aid implementation. Findings from this study will represent transferable knowledge for researchers interested in the mechanisms that affect the success of physical interventions for people with frailty.